Progress of Primary and Upper Primary Education in Jammu and Kashmir: (1950–51 to 2001–02) - Karihaloo, Sarla (JOURNAL OF INDIAN EDUCATION, 2010)
The spread of education and educational facilities have made great strides in the state during the past decades of planned development. A Considerable educational facility has been made available in the remote backward and hilly areas of the state. In the present paper analysis is made on the trends of students’ enrolment, teacher recruitment and student–teacher ratios with emphasis on the recent years. It examines the actions of the state government to improve the quality of education. The analysis brings forth that the J&K state continues to be educationally backward though female enrolment has shown a significant rise during last few years, and the gender disparity does not seem to be getting reduced. Figures show that there are at least as many girls outside the school as they are inside in the age group of 6–14 years.